2009
DOI: 10.1093/bioinformatics/btp447
|View full text |Cite
|
Sign up to set email alerts
|

FRODOCK: a new approach for fast rotational protein–protein docking

Abstract: http://sbg.cib.csic.es/Software/FRODOCK/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 36 publications
0
122
0
1
Order By: Relevance
“…This is a limitation of any FFT-based algorithm, and it was already shown that performing parallel docking runs using several initial rotations provided more consistent docking results than using just a single one. 14 These results suggest that the selected conformers according to specific criteria (i.e. optimal binding energy, number of clashes) were more beneficial for docking than just a random selection of conformers or initial rotations.…”
Section: Selected Conformers Can Yield Significantly Better Docking Rmentioning
confidence: 88%
“…This is a limitation of any FFT-based algorithm, and it was already shown that performing parallel docking runs using several initial rotations provided more consistent docking results than using just a single one. 14 These results suggest that the selected conformers according to specific criteria (i.e. optimal binding energy, number of clashes) were more beneficial for docking than just a random selection of conformers or initial rotations.…”
Section: Selected Conformers Can Yield Significantly Better Docking Rmentioning
confidence: 88%
“…This representation allows rotational searches to be accelerated by angular FFTs, and it enables translations to be calculated analytically in the Fourier basis (15). A similar approach has been developed by Chacon's group (16,17), in which translations are calculated numerically. However, both approaches were found to have lower accuracy than traditional Cartesian FFT sampling (15).…”
Section: Significancementioning
confidence: 99%
“…FTDock (Gabb et al, 1997), ZDock (Mintseris et al, 2007), PIPER (Kozakov et al, 2006)), and by some other very successful geometry-based methods (e.g. FRODOCK (Garzon et al, 2009), Hex (Ritchie and Kemp, 2000), MolFit (Katchalski-Katzir et al, 1992)). A docking procedure usually involves several steps (Vajda and Kozakov, 2009).…”
Section: Protein-protein Dockingmentioning
confidence: 99%